Monitoring Korosi Discharge Conveyor E pada Tambang Batubara PT GHI di Kabupaten Banjar Provinsi Kalimantan Selatan - Adinda Pratiwi Fitrianingsih; Elfida Moralista; Zaenal (Bandung Conference Series: Mining Engineering, 2023)
Abstract. PT GHI's coal mine located in Banjar Regency, South Kalimantan Province, a conveyor is used to transporting coal. Conveyor is conveyance that functions to move material to another place continuously. The conveyor structure which is made of carbon steel has the potential to experience corrosion, it has an impact on the Remaining Service Life of conveyor structure. This research activity was carried out to investigate the types of corrosion that occur and corrosion control methods, Corrosion Rate, and Remaining Service Life on the conveyor structure. The methodology used in this study is the measurement of the thickness reduction of the conveyor structure. The 95 meter long conveyor structure consisting of 3 segments with 25 test points was measured for thickness using the Smart Sensor Ultrasonic Thickness Gauge TT130. The output of this tool is the actual thickness value which is then used to determine Corrosion Rate and Remaining Service Life. The environmental conditions in the study area in 2015 – 2020 have average rainfall of 218.32 mm/year, average relative humidity of 81.37%, and average temperature of 25.92oC. The type of corrosion that occurs in the conveyor structure is uniform corrosion. The corrosion control method used is three-layer coating system, namely primary coating using Seaguard 5000, intermediate coating using Sherglass FF, and top coating using Aliphatic Acrylic Modified Polyurethane. Based on data processing, the Corrosion Rate was obtained between 0.1757 – 0.3014 mm/year which indicates that relative corrosion resistance of steel is included in good category and Remaining Service Life is between 7.03 – 10.09 years. The number of test points predicted not to reach the design life is 9 test points or 36% of the total test points. Abstrak. Pada tambang Batubara PT GHI yang berlokasi di Kabupaten Banjar, Provinsi Kalimantan Selatan menggunakan alat conveyor sebagai alat pengangkutan batubara. Conveyor adalah salah satu alat angkut yang berfungsi untuk memindahkan material dari suatu tempat menuju tempat lainnya yang bersifat kontiyu. Struktur conveyor yang tebuat dari baja karbon berpotensi mengalami korosi sehingga berdampak terhadap Remaining Service Life struktur conveyor tersebut. Kegiatan penelitian ini dilakukan untuk menyelidiki jenis korosi yang terjadi dan metode pengendalian korosi, Corrosion Rate, dan Remaining Service Life pada struktur conveyor. Metodologi penelitian adalah dengan pengukuran pengurangan ketebalan struktur conveyor. Struktur conveyor sepanjang 95 meter yang terdiri atas 3 segmen dengan 25 test point diukur ketebalannya menggunakan alat Smart Sensor Ultrasonic Thickness Gauge TT 130. Output dari alat ini yaitu nilai tebal aktual yang selanjutnya nilai tersebut digunakan untuk menentukan Corrosion Rate dan Remaining Service Life. Adapun kondisi lingkungan pada daerah penelitian pada tahun 2015 – 2020 memiliki curah hujan rata-rata 218,32 mm/tahun, kelembapan relatif rata-rata 81,37%, dan temperatur rata-rata 25,92oC. Jenis korosi yang terjadi pada struktur conveyor merupakan korosi merata. Metode pengendalian korosi yang digunakan adalah metode coating sistem three layers yaitu primer coating menggunakan Seaguard 5000, intermediate coating menggunakan Sherglass FF, dan top coating menggunakan Aliphatic Acrylic Modified Polyurethane. Berdasarkan pengolahan data diperoleh Corrosion Rate antara 0,1757 – 0,3014 mm/tahun yang menunjukkan bahwa ketahanan korosi relatif baja termasuk pada kategori good dan Remaining Service Life antara 7,03 – 10,09 tahun. Jumlah test point yang diprediksi tidak dapat mencapai umur desain yakni 9 test point atau 36% dari keseluruhan test point.